Pogląd prawosławnych rosyjskich pedagogów na metody wychowawcze według systemu pedagogicznego Johanna Friedricha Herbarta : ВЗГЛЯД РОССИЙСКИХ ПРАВОСЛАВНЫХ ПЕДАГОГОВ НА МЕТОДЫ ВОСПИТАНИЯ СОГЛАСНО ПЕДАГОГИЧЕСКОЙ СИСТЕМЕ ИОГАННА ФРИДРИХА ГЕРБАРТА - Bojcheniuk , Jurij (Seminare. Poszukiwania naukowe, 2022)
The article presents the main psychological foundations of the system of child education worked out by J. F. Herbart, who paid special attention to the development of a child’s character by applying five principles and recognizing the need for grading (six steps of education). Some of J. F. Herbart’s psychological views are criticized by Russian Orthodox educationists: his concept of the newborn child’s soul as a tabula rasa, the will being supposedly subject to education and the desire as not existing independently of the reflexes of the soul. Orthodox educationists, moreover, disagree with all the five principles of forming a child’s character. They most strongly object to the idea of conciliating believers and non-believers or the righteous and sinners. In relation to the steps of a child’s education and other pedagogical claims of the German scholar, Orthodox educationalists voice their objections particularly to the view that a child’s religious feelings should be developed at a later stage of life and that those feelings can be transferred from family feelings. Likewise, they disagree with the approach of the German educationist as to the content of religious education and express their critical comments on his views concerning a child’s individuality.